2018
DOI: 10.1038/s41598-018-34174-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Trichuris suis excretory/secretory proteins as a function of life cycle stage and their immunomodulatory properties

Abstract: Parasitic worms have a remarkable ability to modulate host immune responses through several mechanisms including excreted/secreted proteins (ESP), yet the exact nature of these proteins and their targets often remains elusive. Here, we performed mass spectrometry analyses of ESP (TsESP) from larval and adult stages of the pig whipworm Trichuris suis (Ts) and identified ~350 proteins. Transcriptomic analyses revealed large subsets of differentially expressed genes in the various life cycle stages of the parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 115 publications
0
45
0
Order By: Relevance
“…Hatching of infective T. suis eggs in the pig intestine and the parasitic invasion of the mucosal layer and epithelial cells in the proximal colon to initiate intracellular larval feeding and development perturbs the cytoskeleton matrix and cell junctions 67 . These early events alter the local microbiome as parasite mucolytic components released during larval invasion provide substrates to expand bacteria such as the Mucispirillum 16 , and parasite products that facilitate tissue penetration and worm metabolism activate and react to host immune protective responses 68 . The interplay of host, parasite, and microbiome has consequences for parasite survival and the intensity and persistence of host inflammation 16 18 The earliest events recorded in this current study showed that at 21 DAI there was an induction of gene expression to activate type 2 related immune responses including M2a macrophage that have been shown to regulate intestinal smooth muscle function via SERPINB2 36 , and that has been linked to a STAT6-dependent effects on smooth muscle hyper-contractility associated with protection against T. muris in mice (Madden et al, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Hatching of infective T. suis eggs in the pig intestine and the parasitic invasion of the mucosal layer and epithelial cells in the proximal colon to initiate intracellular larval feeding and development perturbs the cytoskeleton matrix and cell junctions 67 . These early events alter the local microbiome as parasite mucolytic components released during larval invasion provide substrates to expand bacteria such as the Mucispirillum 16 , and parasite products that facilitate tissue penetration and worm metabolism activate and react to host immune protective responses 68 . The interplay of host, parasite, and microbiome has consequences for parasite survival and the intensity and persistence of host inflammation 16 18 The earliest events recorded in this current study showed that at 21 DAI there was an induction of gene expression to activate type 2 related immune responses including M2a macrophage that have been shown to regulate intestinal smooth muscle function via SERPINB2 36 , and that has been linked to a STAT6-dependent effects on smooth muscle hyper-contractility associated with protection against T. muris in mice (Madden et al, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…In order to persist in their host, whipworms modulate intestinal inflammation, ensuring their host’s and their own survival ( Klementowicz et al, 2012 , Grencis, 2015 ). One such mechanism of immunomodulation is the release of ES products that can interact with immune cells, the regulatory impact of which has been described ( Kuijk et al, 2012 , Klaver et al, 2013 , Laan et al, 2017 , Leroux et al, 2018 , Shears et al, 2018b , Bancroft et al, 2019 ). ES products likely act also on caecal IECs, given that whipworms live inside the epithelium; however, little is known about these interactions ( Hiemstra et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Whipworms can remain in their host for years, causing chronic infections. To optimise their residence in their hosts, whipworms manipulate host inflammation, partly through the immunoregulatory effects of ES products released by the parasites ( Kuijk et al, 2012 , Klaver et al, 2013 , Hansen et al, 2015 , Laan et al, 2017 , Tritten et al, 2017 , Eichenberger et al, 2018b , Leroux et al, 2018 , Shears et al, 2018a , Shears et al, 2018b , Bancroft et al, 2019 ). Progress has been made in understanding the composition and anti-inflammatory actions of whipworm ES products.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic worms have a remarkable ability to modulate the host immune response through several mechanisms; speci c parasitederived proteins can modulate immune functions playing an important role in the parasite-host interaction. Excretion/secretion proteins from larvae and adults of the porcine whipworm, T. suis, closely related to the human T. trichiura, were investigated by Leroux et al [21], who identi ed a subset of proteins that promote speci c anti-in ammatory functions and immunomodulatory properties.…”
Section: Antigenic Pro Le Of T Trichiura Ee and Fe Extracts And Idenmentioning
confidence: 99%
“…Only a few reports indicate that they may be modulators of the immune system, and recognize them as potential sources of diagnostic antigens [17,18]. Interestingly, the administration of embryonated eggs from the animal species Trichuris suis or Trichuris muris to humans has been described as potential therapeutic agents for immune-related pathologies such as chronic intestinal in ammatory diseases, emphasizing their capacity to downregulate aberrant intestinal in ammation [6,[19][20][21][22]. Their immunomodulatory capacity continues to be investigated with some studies trying to identify the molecules responsible for those effects [14,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%